Length-weight relationships of four fish species from a coastal artisanal fishery, southern Bangladesh - Siddik, Muhammad Abu Bakar; Chaklader, M.; Hanif, M.; Islam, M.; Fotedar, Ravi (2016)
This study presents the first report of length–weight relationships (LWRs) for Apocryptes bato (Hamilton, 1822), Salmophasia phulo (Hamilton, 1822), and Silonia silondia (Hamilton, 1822), excluding Anodontostoma chacunda (Hamilton, 1822), from fishermen’s catches landed in a coastal artisanal fishery at Patuakhali, Southern Bangladesh. Specimens were sampled occasionally over a period of 1 year between August 2014 and September 2015. Fishes were collected from coastal fishermen using cast nets (mesh size <0.5 cm) for A. bato, set bag nets (mesh size 0.5 cm) for A. chacunda and S. silondia, and lift nets (mesh size <0.5 cm) for S. phulo. The LWRs obtained were W = 0.006L2.99, (r2) = 0.976, W = 0.011L3.04, (r2) = 0.971, W = 0.006L3.00, (r2) = 0.945 and W = 0.007L2.99, (r2) = 0.988 for A. bato, A. chacunda, S. phulo, and S. silondia, respectively.